Add 7 and 7 which is 14 and then take it apart because it is an even number
complementary angles add up to 90°, so therefore we know that ∡A + ∡B = 90°, and also they are in a ratio of 3:6.
![\bf \cfrac{A}{B}=\cfrac{3}{6}\implies \cfrac{A}{B}=\cfrac{1}{2}\implies 2A=\boxed{B} \\\\[-0.35em] ~\dotfill\\\\ A+B=90\implies A+\boxed{2A}=90\implies 3A=90\\\\\\ A=\cfrac{90}{3}\implies \blacktriangleright A=30 \blacktriangleleft \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ 2(30)=B\implies \blacktriangleright 60=B \blacktriangleleft](https://tex.z-dn.net/?f=%5Cbf%20%5Ccfrac%7BA%7D%7BB%7D%3D%5Ccfrac%7B3%7D%7B6%7D%5Cimplies%20%5Ccfrac%7BA%7D%7BB%7D%3D%5Ccfrac%7B1%7D%7B2%7D%5Cimplies%202A%3D%5Cboxed%7BB%7D%0A%5C%5C%5C%5C%5B-0.35em%5D%0A~%5Cdotfill%5C%5C%5C%5C%0AA%2BB%3D90%5Cimplies%20A%2B%5Cboxed%7B2A%7D%3D90%5Cimplies%203A%3D90%5C%5C%5C%5C%5C%5C%20A%3D%5Ccfrac%7B90%7D%7B3%7D%5Cimplies%20%5Cblacktriangleright%20A%3D30%20%5Cblacktriangleleft%0A%5C%5C%5C%5C%5B-0.35em%5D%0A%5Crule%7B34em%7D%7B0.25pt%7D%5C%5C%5C%5C%0A2%2830%29%3DB%5Cimplies%20%5Cblacktriangleright%2060%3DB%20%5Cblacktriangleleft)
Answer:
Angles in a triangles add up to 180°
Respectively 1 : 2 : 3 is going to be 1 x , 2 x and 3 x so,
1 x + 2 x + 3 x = 180°
⇒ Simplify
6 x = 180°
⇒ Divide by 6 on both sides to isolate x
x = 30°
Since the ratio was 1 x : 2 x : 3 x and x is 30°,
30 : 60 : 90
And since there is a 90° angle, it is a right - angled triangle
Answer:
(x+4)(6x^2 - 7)
Step-by-step explanation:
Focus on the first 2 terms first and on the second 2 terms last:
6x^3 + 24x^2 = 6x^2(x+4)
-7x-28 = -7(x+4)
We see that the factor (x+4) is common to both pairs: common to the first 2 terms and common to the last 2 terms.
Thus,
6x³ + 24x² -7x -28 = (x+4)(6x^2 - 7(x+4)
Factoring out x+4, we get (6x^2 - 7), and so 6x³ + 24x² -7x -28 in factored form is (x+4)(6x^2 - 7).